Rancangan Tata Letak Fasilitas Untuk Meminimalkan Jarak Material Handling (Studi Kasus CV. Dholpin Industries) - Putri, Azizah Asmi; Suhartini, Suhartini (Matrik : Jurnal Manajemen dan Teknik Industri Produksi, 2024)
Dholpin Industries is a manufacturing company that produces furniture. This research aims to improve and create a new layout design for CV. Dholpin Industries, which considers the optimal material handling movement distance, creates alternative layout designs and compares distances from the initial and proposed layouts. This research uses the Systematic Layout Planning (SLP) method, Blocplan Software, and the Computerized Relationship Layout Planning (CORELAP) algorithm. The results of calculating the material handling movement distance in the initial layout were 193,116 m; in the proposed layout using the Systematic Layout Planning (SLP) method, it was 168,278 m; in the Blocplan Software, it was 139,348 m; and in the Computerized Relationship Layout Planning (CORELAP) Algorithm it was 130,240 m. Then, the most optimal namely using the Computerized Relationship Layout Planning (CORELAP) Algorithm method with distance saving 62.876 m.